2017
DOI: 10.12669/pjms.332.12084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, side effects and awareness about energy drinks among the female university students in Saudi Arabia

Abstract: Objective:To evaluate the consumption, prevalence, side effects and awareness of energy drinks among female university students in Saudi Arabia.Methods:A quantitative research design was implied with sample size of 358 female students, recruited from Prince Sattam bin Abdulaziz University. The data, gathered through self-administered questionnaire, was analyzed through SPSS version 20.0 with p value <0.005 deemed statistically significant.Results:From the sample of 358 female students, 337 attempted the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
4
36
0
2
Order By: Relevance
“…The epidemic of energy drinks consumption is also widely spread in the Saudi community, as Saudi Arabia is classified among the top ten countries when it comes to energy drinks consumption (Rahamathulla, 2017). In this study, we aimed at investigating and comparing the hazardous effects of chronic consumption of energy and soft drinks on the biochemical and histological level in rat animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemic of energy drinks consumption is also widely spread in the Saudi community, as Saudi Arabia is classified among the top ten countries when it comes to energy drinks consumption (Rahamathulla, 2017). In this study, we aimed at investigating and comparing the hazardous effects of chronic consumption of energy and soft drinks on the biochemical and histological level in rat animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigation (questionnaire study, n = 488), about 10% of young adults complained of such health problems occurring after consumption of EDs, including: abdominal pains, arrhythmia and nausea [ 37 ]. A survey done by Rahamathulla showed that among students declaring consumption of EDs ( n = 274), the most common side effects were headache (32%), stomachache (21%), increased urination (11.2%), restlessness (9.7%), hypertension (9.1%), tingling (7.1%) and nervousness (6%) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase of production and marketing has made ED easily available and accessible at local shops as well as at university campuses [2]. Nowadays, ED consumption among adolescents and young adults has become a common practice.…”
Section: Discussionmentioning
confidence: 99%
“…Beverages marketed as "energy drinks" are nonalcoholic fluids that contain stimulants, mainly caffeine, and generally claim to provide an extra burst of energy to perform well through the day [1]. Nowadays, there has been an increase in the consumption of energy drinks (ED), and consuming these beverages has become a common practice, especially among younger adults [2]. Although ED contains a large dose of caffeine, some other stimulants such as taurine, glucuronolactone, B group vitamins, inositol, niacin and panthenol can be present according to brand and type [3,4].…”
Section: Introductionmentioning
confidence: 99%